Determinants of the credit cycle: A flow analysis of the extensive margin - Vincenzo Cuciniello; Nicola Di Iasio (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2021)
Using loan-level data covering almost all loans to households and businesses from banks in Italy over the past 20 years, we offer new empirical evidence that credit declines during a recession primarily because of the reduction in the net creation of borrowers. We then build on a flow approach to decompose the net creation of borrowers into gross flows across three statuses: (i) borrower, (ii) applicant and (iii) neither borrower nor applicant (i.e. inactive firms or households in the bank credit market). Along the macroeconomic dimension of these gross flows, we document four cyclical facts. First, fluctuations in the number of new borrowers (inflows) account for the bulk of volatility in the net creation of borrowers. Second, the volatility of borrower inflows is two times as large as the volatility of obligors exiting from the credit market (outflows). Third, borrower inflows are highly procyclical and tend to lead the business cycle. Fourth, decreases in the probability of a match between borrower and lender during recessions are a leading explanation for the role of borrower inflows.
Keywords: E51; E32; E44; 330; Borrower flows; business cycles; credit cycles; credit market participation